Knowledge of Radiographiers about radiation protection procedures. - Khan, Abdur Rehman; Shah, Syed Afaq Hussain (Journal of Postgraduate Medical Institute, 2011)
to assess the knowledge of radiogrpahers radiatio0n protection in diagnsotic radiology. Questions were asked from radiographers of three tertiary care hospitals of Peshawar in November 2005. All radiolographers were interviewed by the author according to pre-prepared questionnaire. Questions pertained to principles of radiation protection, permissible occupational dosage, permissible dose for general propulation, use of fool switch in fluoroscopy, advantage o0f collimation and effect of increasin Kilo Voltage Peak (KVP) on patients dose. Sampling was convenience sampling. Knowledge of radiographers regarding radiation protection procedures and principles was poor.